Multisensor monitoring and data integration reveal cyclical destabilization of Äußeres Hochebenkar Rock Glacier - Hartl, Lea; Zieher, Thomas; Bremer, Magnus; Stocker-Waldhuber, Martin; Zahs, Vivien; Höfle, Bernhard; Kluge, Christoph; Cicoira, Alessandro (Earth surface dynamics, 2023)
This study investigates rock glacier destabilization based on the results of a unique in situ and remote sensing-based monitoring network focused on the kinematics of the rock glacier in Äußeres Hochebenkar (Austrian Alps). We consolidate, homogenize, and extend existing time series to generate a comprehensive dataset consisting of 14 digital surface models covering a 68 year time period, as well as in situ measurements of block displacement since the early 1950s. The digital surface models are derived from historical aerial imagery and, more recently, airborne and uncrewed aerial vehicle-based laser scanning (ALS, ULS). Since 2017, high-resolution 3D ALS and ULS point clouds are available at annual temporal resolution. Additional terrestrial laser scanning data collected in bi-weekly intervals during the summer of 2019 is available from the rock glacier front. Using image correlation techniques, we derive velocity vectors from the digital surface models, thereby adding rock glacier-wide spatial context to the point scale block displacement measurements. Based on velocities, surface elevation change, analysis of morphological features, and computations of the bulk creep factor and strain rates, we assess the combined datasets in terms of rock glacier destabilization. To additionally investigate potential rotational components of the movement of the destabilized section of the rock glacier, we integrate in situ data of block displacement with ULS point clouds and compute changes in the rotation angles of single blocks during recent years. The time series shows two cycles of destabilization in the lower section of the rock glacier. The first lasted from the early 1950s until the mid 1970s. The second began around 2017 after approximately two decades of more gradual acceleration and is currently ongoing. Both destabilization periods are characterized by high velocities and the development of morphological destabilization features on the rock glacier surface. Acceleration in the most recent years has been very pronounced, with velocities reaching 20–30 m/a in 2020/21. These values are unprecedented in the time series and suggest highly destabilized conditions in the lower section of the rock glacier, which shows signs of translational as well as rotational, landslide-like movement. Due to the length and granularity of the time series, the cyclic destabilization process at Äußeres Hochebenkar rock glacier is well resolved in the dataset. Our study highlights the importance of interdisciplinary, long-term and continuous, high-resolution 3D monitoring to improve process understanding and model development related to rock glacier rheology and destabilization.